2012
DOI: 10.1007/s11434-012-5540-1
|View full text |Cite
|
Sign up to set email alerts
|

Projected change in the relationship between East Asian summer rainfall and upper-tropospheric westerly jet

Abstract: The authors analyzed the interannual variability in summer precipitation and the East Asian upper-tropospheric jet (EAJ) over East Asia under the Historical and Representative Concentration Pathways Scenarios (RCPs, including RCP4.5 and RCP8.5), using outputs of 17 Coupled Model Intercomparison Project phase 5 (CMIP5) coupled models. The analyzed results indicate that the models can reasonably reproduce relatively stronger interannual variability in both East Asian summer rainfall (EASR) and EAJ. These models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Zhang and Guo () suggest that the summer SWJ will strengthen and migrate southwards over eastern Asia in the future under the warming background scenario. Dai and Lu () point out that the relationship between the East Asian rainfall and the meridional displacement of the East Asian Jet is projected to be stronger in the 21st century under the different global warming scenarios. Sea surface temperature (SST) warming is a prominent feature of global warming.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Guo () suggest that the summer SWJ will strengthen and migrate southwards over eastern Asia in the future under the warming background scenario. Dai and Lu () point out that the relationship between the East Asian rainfall and the meridional displacement of the East Asian Jet is projected to be stronger in the 21st century under the different global warming scenarios. Sea surface temperature (SST) warming is a prominent feature of global warming.…”
Section: Introductionmentioning
confidence: 99%
“…Following Guo et al (), Huang and Liu () revealed that the climatological mean state of the EASJ, including its intensity, location and seasonal evolution, is well portrayed in the AM2.1, a model developed at NOAA's Geophysical Fluid Dynamics Laboratory (GFDL). Dai and Lu () investigated the temporal‐spatial features of East Asia summer rainfall and the EASJ in 17 models from the Coupled Model Intercomparison Project Phase 5 (CMIP5) and found that the models capture the interannual variability of rainfall in East Asia and Northwest Pacific and that of the EASJ; the correlation between the precipitation anomaly and the meridional displacement of the EASJ is also reproduced.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the projections of CMIP5 models, Horinouchi et al (2019) suggested that the climatological changes of the EAJ show a weakly southward shift. In addition, Dai and Lu (2012) suggested that the relationship between the inter-annual variabilities in EASM rainfall and EAJ becomes stronger under global warming.…”
mentioning
confidence: 99%